Design of a Telemetry System for Monitoring Miniature Steam Power Plants - Pradina, Ilham; Nursusanto, Usman (Energy Insights, 2025)
This final project aims to design and develop an Internet of Things (IoT)-based monitoring system for a miniature Steam Power Plant (PLTU) capable of monitoring key parameters such as voltage, current, power, pressure, and temperature in real time. The main objectives of this project are: (1) to design an IoT-based miniature PLTU monitoring system; (2) to determine the functional test results of the monitoring system; and (3) to evaluate the system’s performance in monitoring electrical and thermal parameters. The development stages include needs identification, system design, device fabrication, testing, and result evaluation. Testing was conducted at the Repair Laboratory, Department of Electrical and Electronics Engineering. Functional test results show that all telemetry system components worked properly. The pressure sensor recorded up to 5.6 bar with fast response, while the RTD PT100 temperature sensor measured up to 124°C with an error of <0.06%. The PZEM-017 sensor measured voltage with a deviation of ±0.13 V, current ±0.02 A, and power ±0.2 W. The system reliably monitored parameters during 30 minutes of heating. The DC generator produced up to 16.7 V and 2.6 W of power. The system proved to be responsive, accurate, and effective as an educational tool for energy conversion and IoT-based monitoring.